Efektivitas Teknik Token Economy dalam Meningkatkan Perilaku Membuang Sampah Pada Tempatnya di SDN Mekar Martapura Timur - Rika Vira Zwagery; Nor Mai Leza (Jurnal Ilmiah Psikologi MIND SET, 2020)
These days, the littering behavior is still become a problem in the society. One of the solution is to implanted good littering behavior in children. Therefore, parents and the environment play an important role in teaching and modeling good behavior. One of method that can be applied to foster children motivation for maintain environmental hygiene is by modifying behavior with used of token economy. This study aims to determined the effectiveness of token economy techniques for improving littering behavior at SDN Mekar Martapura Timur. This study used a quasi-experimental method with one group pretest-posttest design. The sampling technique used purposive sampling by taking grade IV students totaling 30 people as research subjects. The data analysis method used is a comparative test to compare pre-test and post-test. The results of the study through paired t-tests obtained sig. 0.000 <0.05, which means that there are differences in littering behavior of students before and after the implementation of economic tokens, this showed that economic tokens method can improve the littering behavior of the students at SDN Mekar Martapura Timur.